The fish fauna in tropical rivers: The case of the Sorocaba river basin, São Paulo, Brazil - Smith, Welber Senteio (2003)
A survey was carried out on the fish species in the Sorocaba River basin, the main tributary of the left margin of the Tietê River, located in the State of São Paulo, Brazil. The species were collected with gill nets. After identification of the specimens, their relative abundance, weight and standard length were determined. Up to the present moment there are not any studies that focus this subject in this hydrographic basin. Fifty-three species, distributed in eighteen families and six orders were collected. Characiformes were represented by twenty-eight species, Siluriformes by seventeen species, the Gymnotiformes by three species, Perciformes and Cyprinodontiformes by two species, and the Synbranchiformes by one species. Among the collected species there were two exotic. The most abundant species were Astyanax fasciatus and Hypostomus ancistroides. In relation to total weight the most representative species were Hoplias malabaricus and Hypostomus ancistroides. Cyprinus carpio, Prochilodus lineatus, Schizodon nasutus and Hoplias malabaricus were the most representative species in relation to average weight. Largest standard length were recorded for Sternopygus macrurus, Steindachnerina insculpta, Eigenmannia off. virescens and Cyprinus carpio.